Case Report: unexpected cause of cyanosis in an infant after acute exposure to high altitude—severe tricuspid regurgitation secondary to tricuspid valve prolapse - Cui, Yaru; Yang, Lixia; Wu, Ping; Shao, Shuran; Luo, Shuhua; Zhou, Kaiyu; Liu, Xiaoliang; Wang, Chuan; Duan, Hongyu (Frontiers in Cardiovascular Medicine, 2024)
Background: Severe tricuspid regurgitation (TR) causing cyanosis with patent foramen ovale (PFO) and right-to-left atrial shunting requires a precise diagnosis for optimal therapy. Tricuspid valve prolapse (TVP) can lead to TR and is sometimes overlooked, especially in complex cases with factors like pulmonary hypertension (PH). We present an infant with cyanosis and profound TR after high-altitude exposure, initially misattributed to PH but found to be primarily due to spontaneous chordae tendineae rupture and TVP. This case underscores the challenges in diagnosing TR-induced cyanosis.The 3-month-old infant rapidly developed cyanosis, hypoxemia, right atrial enlargement, severe tricuspid regurgitation (TR), and patent foramen ovale (PFO) shunting after high-altitude exposure. Although echocardiography revealed tricuspid valve prolapse (TVP), initial consideration linked TR and right-to-left shunting to pulmonary hypertension (PH) due to the temporal correlation with rapid altitude exposure. Despite hemodynamic stability and absence of respiratory distress after respiratory support and combined PH medication therapy, the persistent hypoxemia did not reverse as expected. This treatment outcome and repeated echocardiograms reminded us that TR was primarily caused by TVP rather than PH alone. IIntraoperative exploration confirmed that TVP was caused by a rupture of TV chordae tendineae and anterior papillary muscle head, and the chordae tendineae/papillary muscle connection was reconstructed. After surgery, this patient was noncyanotic with an excellent long-term prognosis, a trivial TR with normal TV function being observed echocardiographically.Conclusions: TR-induced cyanosis can be not only a consequence of PH and right-sided heart dilation but also a primary condition. Repetitive reassessment should be undertaken with caution, particularly when patients are not improving on therapy in the setting of conditions known to predisposition to secondary TR. Since TVP caused by rupture of the chordae or papillary muscles is rare but fatal in children, early diagnosis is clinically substantial to proper management and satisfactory long-term outcomes.